Inflammatory bowel disease in C.B-17 scid mice reconstituted with the CD45RBhigh subset of CD4+ T cells. - Leach, M; Bean, A; Mauze, S; Coffman, R; Powrie, F (1996)
Chronic inflammation developed spontaneously in the large intestine of C.B-17 scid mice restored with the CD45RBhigh subset of CD4+ T cells obtained from normal BALB/c mice. The inflammation, which extended diffusely from the cecum to the rectum, was localized to the lamina propria of mildly affected mice but became transmural in severely affected mice. Immunohistochemical and flow cytometric analyses showed that the inflammatory infiltrate contained numerous macrophages accompanied by moderate numbers of activated CD4+ lymphocytes. Some mice also had scattered multinucleated giant cells. Mucin depletion and epithelial hyperplasia resulting in glandular elongation and mucosal thickening were also consistently seen. Less frequent findings included ulceration with fibrosis, crypt abscesses, crypt loss, and granulomatous inflammation. Immunofluorescent analysis of inflamed large intestinal sections demonstrated increased epithelial expression of major histocompatibility class II antigens. The changes in the large intestine of these mice are similar to those seen in patients with idiopathic inflammatory bowel disease (Crohn's disease and ulcerative colitis). This murine model may be useful for studying mucosal immunoregulation as it relates to the pathogenesis and treatment of chronic inflammatory bowel diseases in the large intestine of human patients.